PENDIDIKAN TOLERANSI BERAGAMA PERSPEKTIF TUJUAN PENDIDIKAN ISLAM - Kurnia Muhajarah (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2016)
This research was motivated by the events of a religious conflict between people of different religions in Indonesia. This study is intended to answer the question of how is the concept of religious tolerance education and how is the educational relevance of religious tolerance with the aim of Islamic education. The issues discussed with the primary data, books or literature research studies. During data collection, the researchers take steps through library research and when analyzing the data, researchers used an inductive method and the comparative method. This study shows that Islam commands his people to be tolerant, not only in Judaism and Christianity, but also to religions other. Surat al-Baqarah verse 256 say that there is no compulsion about religion because the straight and true path has been clearly distinct from the wrong and misguided. Whatever the man can chose the way that he wants. If the concept of religious tolerance education linked to the aims of Islamic education, the purpose of the educational concept of religious tolerance they are: a) that Muslims have the ability to develop their potential, useful for others and society. b) to build the Islamic society who have a certain al-karimah. c) to build the Islamic society that is smart in faith and piety. Thus, the concept of religious tolerance education is in according to the objectives of Islamic education.